Analisis faktor-faktor kunci efektivitas saluran distribusi susu steril (Studi kasus: Bear Brand PT. Nestle Indonesia) - Akbar Bimo Prastio; Novie Andri Setianto; Yusmi Nur Wakhidati; Ade Banani; Dindy Darmawati Putri (Journal of Agribusiness Science and Rural Development, 2026)
As a competitive sterilized milk brand in the Indonesian market, Bear Brand heavily relies on its product distribution process to reach consumers. The involvement of distributors in 65% of the channeling process creates a diverse and complex network of distribution channels.The primary objective of this study was to examine the efficiency of Nestle's distribution and to identify critical product attributes that influence channel effectiveness. A survey method was employed in DKI Jakarta, utilizing a sample of 100 intermediary traders drawn from a population of 28,808 outlets. The research instrument was confirmed to be reliable and valid (Cronbach's Alpha > 0.80). The main data analysis utilized Factor Analysis, which was deemed suitable (Kaiser-Meyer-Olkin (KMO) = 0.629), successfully grouping 20 distribution attributes into six principal factors. The results indicate that distribution effectiveness is significantly driven by financial aspects. The three most dominant factors identified were the Profit Margin Factor (supported by adequate profit margin 0.70 and affordable price 0.66), the Price Structure Factor (0.70), and the Product Quality Factor (good product quality 0.60). Supporting factors, such as easy sales requirements (0.62) and daily product availability (0.50), were also significant, whereas the Communication and Information Factor showed a weak correlation (0.35). In conclusion, profitability and quality are the main keys to the success of the Bear Brand distribution channel. Therefore, it is recommended that Nestle strengthen the Profit Margin and Price Structure Factors while simultaneously improving ease of transaction and reviewing the effectiveness of information delivery to distributor.